Estimating the appropriate quantity of settlement balances in a floor system - Narayan Bulusu; Matthew McNeely; Kaetlynd McRae; Jonathan Witmer (Bank of Canada, 2023)
In April 2022, the Bank of Canada announced that it would continue to use a floor system to implement monetary policy by providing a sufficiently large quantity of settlement balances to enable the overnight repo rate to trade at close to the deposit rate. In contrast, the Bank's guiding principles of prudence, transparency and neutrality, which govern the management of its balance sheet, favour maintaining settlement balances as low as possible. In this context, this paper describes two complementary approaches to estimating the appropriate quantity of settlement balances needed to effectively maintain a floor system. The first is a regressionbased analysis to estimate the quantity required to maintain the overnight repo rate close to the Bank's policy interest rate (which is equal to the deposit rate in a floor system). The second is an analysis of operational considerations in implementing a floor system in Canada. Both approaches highlight that considerable uncertainty exists in determining the demand for settlement balances. Such uncertainty emphasizes the need for the Bank to monitor money market conditions as it continues to normalize its balance sheet after undertaking quantitative easing operations related to the COVID-19 pandemic.
Keywords: E41; E42; E52; E58; G21; G28; 330; Financial institutions; Financial markets; Financial system regulation and policies; Monetary policy implementation; Payment clearing and settlement systems